Environmental variability and intraspecies diversification in Arctic charr (Salvelinus alpinus) - Michaud, Wendy (University of Waterloo, 2016)
Arctic charr (Salvelinus alpinus) exhibit what is arguably the greatest observed range of phenotypic and ecological diversity within a single vertebrate species. The patterns of adaptive diversity that have developed among populations over evolutionary timescales have been well studied in this species. However, much less is known about the patterns of diversification occurring within populations over contemporary timescales. To better understand the mechanisms involved in the processes of diversification and speciation, this thesis investigates the relationship between environmental variability and phenotypic diversity of Arctic charr over different spatial and temporal scales. To examine the relationship between environmental variability and phenotypic diversity over contemporary time scales, we tested the prediction that shifts in the growth patterns of wild Arctic charr would coincide with temperature fluctuations over a 29-year period. A significant portion of the variation in size-at-age among cohorts of Arctic charr was explained by the cumulative lifetime temperatures, but temperature had mixed effects on growth observed within a single growing season. These changes in cohort growth patterns with temperature demonstrated that environmental fluctuations can have cumulative effects on growth dynamics over an individual’s lifetime. However, the observed changes in growth were better explained by the combined coincident changes in species community dynamics, Arctic charr behavioral patterns, and exploitation rates and practices in the Northwest Atlantic region than by the direct effects of temperature fluctuations alone. Phenotypic diversity over a small spatial scale was examined in the context of a polymorphic population of Arctic charr in a high-latitude lake. An unbiased, Bayesian analysis indicated the size-at-age data collected from Lake Hazen was best described by three discrete clusters of individuals. Life history, diet, and morphological characteristics observed for two of these clusters were ...